Productivity in the mining industry: measurement and interpretation - Topp, V.; Soames, L.; Parham, D.; Bloch, Harry (Productivity Commission staff Working Paper, 2008)
The measurement and interpretation of productivity frequently presents significantchallenges, especially when conducted at the industry level. In this regard themining industry is no exception. This report identifies measurement andinterpretation issues of relevance to productivity estimates for the mining industryin Australia. Quantitative evidence is presented regarding the effect on miningindustry productivity growth of two important factors: systematic changes in theunderlying quality of natural resource inputs used in mining; and production lags inresponse to increases in capital investment.